Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/jcbfm.2013.51
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Potentially Salvageable Tissue with MRI-Based Predictive Algorithms after Experimental Ischemic Stroke

Abstract: Individualized stroke treatment decisions can be improved by accurate identification of the extent of salvageable tissue. Magnetic resonance imaging (MRI)-based approaches, including measurement of a 'perfusion-diffusion mismatch' and calculation of infarction probability, allow assessment of tissue-at-risk; however, the ability to explicitly depict potentially salvageable tissue remains uncertain. In this study, five predictive algorithms (generalized linear model (GLM), generalized additive model, support ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 42 publications
3
55
1
Order By: Relevance
“…This has been recently done in the field of medical imaging where the prevalence of diseased voxels after stroke is usually low. The AUC gave a biased view of the model predictive performance, whereas the AUPRC reflected better the quality of the prediction of the diseased volumes [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been recently done in the field of medical imaging where the prevalence of diseased voxels after stroke is usually low. The AUC gave a biased view of the model predictive performance, whereas the AUPRC reflected better the quality of the prediction of the diseased volumes [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have shown that the area under the ROC curve (AUC) and the area under the PR curve (AUPRC) are not equivalent but show very large differences [9]. In the case of rare events, some authors have recommended the use of the AUPRC instead of the AUC [7]; however, up to now, no comparisons are readily available.…”
Section: Introductionmentioning
confidence: 98%
“…10 Perfusion-diffusion mismatch volume was calculated from the difference between the total volumes of ADC and MTT abnormality. The presence of a significant perfusion-diffusion mismatch was confirmed when the MTT-based perfusion lesion volume was 20% larger than the ADC-based tissue lesion volume.…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…Benefit of reperfusion was defined as the absence of lesion growth beyond 10% of the acute ADC-based tissue lesion volume, as measured from the follow-up T 2 lesion volume at poststroke day 7 (calculated as the ipsilateral tissue volume with T 2 values above 2 standard deviations from mean contralateral tissue values 10 ).…”
Section: Image Processing and Analysismentioning
confidence: 99%
“…38 Desai et al 43 showed that prediction could be improved by measuring ADC changes at multiple time points. Wu et al 37 and Bouts et al 44 found high prediction accuracy in rats using a general linear model combining perfusion and diffusion information. Christensen et al 45 have demonstrated increased prediction accuracy of perfusion imaging by more sophisticated CBF parameter analysis.…”
Section: Weaknesses Of Our Studymentioning
confidence: 99%